QUALITY OF LIFE IN PATIENTS WITH OBTURATOR PROSTHESES - Riaz, Nabeela; Warriach, Riaz Ahmad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Oral cancer has a profound impact on the quality of life for patients and their families. Functionally, the mouth is an important organ for speech, swallowing, chewing, taste and salivation. These functions become compromised due to surgical ablation of the tumour. Obturator prosthesis is a common prosthdontic rehabilitative option for maxillectomy patients. The purpose of this study was to investigate how patients with maxillofacial defects evaluate their quality of life after maxillectomy and prosthodontic therapy with obturator prostheses. Methods: Thirty patients were included in the study (11 female, 19 male). The patients were interviewed by using a standardised questionnaire developed by University of Washington (UW-QOL). The detailed questionnaire was adjusted for obturator patients and internalised most parts of obturator functioning scale (OFS). Results: Quality of life after prosthodontic therapy with obturator prostheses was 54±22.9% on average. Functioning of the obturator prosthesis, impairment of ingestion, speech and appearance, the extent of therapy, and the existence of pain had significant impact on the quality of life (p<0.005). Conclusion: Orofacial rehabilitation of patients with maxillofacial defects using obturator prostheses is an appropriate treatment modality. To improve the situation of patients prior to and after maxillectomy sufficient information about the treatment, adequate psychological care and speech therapy should be provided. Keywords: quality of life, maxillectomy, obturator prosthesis, oral cancer, prosthodontic therapy